2021
DOI: 10.3390/biom11111624
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Vitamin D on Immune System and Inflammatory Diseases

Abstract: Immune cells, including dendritic cells, macrophages, and T and B cells, express the vitamin D receptor and 1α-hydroxylase. In vitro studies have shown that 1,25-dihydroxyvitamin D, the active form of vitamin D, has an anti-inflammatory effect. Recent epidemiological evidence has indicated a significant association between vitamin D deficiency and an increased incidence, or aggravation, of infectious diseases and inflammatory autoimmune diseases, such as rheumatoid arthritis, systemic lupus erythematosus, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
145
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 203 publications
(149 citation statements)
references
References 62 publications
2
145
0
2
Order By: Relevance
“…Moreover, levels of Vitamin D are low in diseases that course with hyperinsulinemia such as COVID-19 and in the pathologies that comprise the MS [67,68]. Vitamin D exerts its effects by binding to a nuclear Vitamin D receptor, which is expressed in various immune cells, with particularly high levels in dendritic cells, macrophages, T and B lymphocytes that are increased when the innate immune response is elicited [69].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, levels of Vitamin D are low in diseases that course with hyperinsulinemia such as COVID-19 and in the pathologies that comprise the MS [67,68]. Vitamin D exerts its effects by binding to a nuclear Vitamin D receptor, which is expressed in various immune cells, with particularly high levels in dendritic cells, macrophages, T and B lymphocytes that are increased when the innate immune response is elicited [69].…”
Section: Discussionmentioning
confidence: 99%
“…The enzymes are required to convert the inactive form of vitamin D to the active form of vitamin D where magnesium acts as a cofactor ( 7 , 11 ) ( Figure 2 ). Studies have found the association of vitamin D in improving immune functions ( 22 , 23 ), cell proliferation and organ regeneration ( 24 ), and reducing cardiovascular disease burden ( 25 ), as well as the widely accepted role of vitamin D in vascular, oral and bone health along with calcium metabolism ( 26 30 ). These health benefits of vitamin D will not be achieved even with adequate vitamin D levels if magnesium is deficient, thus emphasizing the essential role of maintaining optimal magnesium levels to attain desirable benefits of vitamin D. Magnesium deficiency is associated with cardiovascular diseases ( 31 ), hypertension ( 32 ), osteoporosis ( 33 , 34 ), and diabetes ( 35 ).…”
Section: Role Of Magnesium In Health and Diseasementioning
confidence: 99%
“…1,25-(OH) 2 D 3 is an important modulator of the immune system, as reflected by the expression of VDR by almost all types of immune cells [ 271 , 272 , 273 ]. 1,25-(OH) 2 D 3 is an enhancer of innate immune reactions against infections and tumor cells by activating the responsive cells (macrophages, natural killer (NK) cells, and neutrophils).…”
Section: Mechanisms Introductionmentioning
confidence: 99%